The Value Relevance of Corporate Social Responsibility (CSR) Assurance - Salman, Manal (Auckland University of Technology, 2016)
This dissertation examines the association between corporate social responsibility (CSR) assurance and firm value. This study contributes to the understanding of the economic benefits inherent in CSR assurance by investigating the incremental value added to firms by assurance. This study also explores CSR assurance quality in both Australia and New Zealand, two countries that are rarely examined. The research adopts a signalling theory view of CSR assurance, where assurance acts as a signal of disclosure quality. The quality of assurance statements has been examined using a content analysis approach. Content analysis generates quality scores that enable quantitative analysis of the effects of CSR assurance quality on firm value. The results show that CSR assurance is value-relevant, but assurance quality is not. Results remained true even after controlling for CSR performance, country and industry effects. The current study also finds that CSR assurance quality is lower when produced by an accountant, and that better governance mechanisms increase assurance statement quality. In addition to the CSR assurance quality score, scholars associate several other attributes with assurance quality. These attributes include the level of assurance and the type of assurance provider. The level of assurance and the type of assurance provider constitute signals about CSR assurance quality. These attributes are also examined to determine their effect on firm value. The results do not show any significant effect of CSR assurance quality on firm value, either from the overall assurance quality score or from the attributes of quality. This research has implications for companies, standard setters and assurance providers. Companies may benefit from adopting CSR assurance. Since the quality of assurance does not communicate any effective signal, it may be important for companies, standard setters and assurance providers to collaborate to improve assurance standards to achieve higher quality, in order to minimise the possibility of falsified signalling through substandard reporting and poor assurance quality. There are many opportunities for future research on the economic benefits of CSR assurance. Future research should look into conducting a longitudinal study on CSR assurance quality. Future research should also examine the effect of assurance and its quality on firm value at different points of time and with various types of CSR disclosure.
Keywords: Corporate Social Responsibility; CSR; Assurance; CSAR; Corporate Social Responsibility Assurance